Chemical Behaviour of CaAg2 under Ethylene Epoxidation Conditions. Issue 35 (26th August 2018) - Antonyshyn, Iryna; Sichevych, Olga; Rasim, Karsten; Ormeci, Alim; Burkhardt, Ulrich; Titlbach, Sven; Schunk, Stephan Andreas; Armbrüster, Marc; Grin, Yuri
Abstract : The binary compound CaAg2 is examined as a catalyst for the ethylene epoxidation reaction. During the induction phase, conversion and selectivity increase and then remain stable for several hundred hours. The presence of ethyl chloride as a promoter is crucial. The pristine CaAg2 reacts with the gaseous reactants and forms a porous microstructure of calcium‐containing oxidation products on the surface, in which particles of elemental silver are embedded. The microstructure is remarkably stable, and in particular, prevents further sintering of the silver particles. Abstract : Oxidation of the intermetallic compound CaAg2 under ethylene epoxidation conditions leads to the formation of a 3D microstructure composed of elemental Ag particles embedded in a less‐crystallized CaO/Ca(OH)2 /CaCO3 support. This ensures enhanced selectivity towards ethylene oxide and prevents the sintering of Ag particles, which is the main reason for the deactivation of industrially used Ag catalysts.